A study on the relationship between the capital structure and financial performance of Takaful companies in Malaysia / Helmi Yusop - Yusop, Helmi (2014)
This research intends to investigate the relationship between capital structure and financial performance of Takaful companies in Malaysia. This study examines the capital structure and profitability of selected Takaful companies in Malaysia during five years which is from year 2008 until 2012. There are twelve companies that offer Takaful products to users but only five Takaful companies involved in this research due to availability of data. Takaful companies involved are HSBC Amanah Takaful (Malaysia) Sdn Bhd, Hong Leong MSIG Takaful, Prudential BSN Takaful, Takaful Ikhlas Berhad and last but not least is Sun Life Malaysia Takaful Berhad. The dependant variable being tested is debt ratio which is expressed by total debt divide by total assets while independent variable is net profit, return on asset (ROA), return on equity (ROE) and last is return on investment (ROI). The final result shows that there is a negative relationship between net profit and capital structure while return on assets (ROA), return on equity (ROE) and return on investment (ROI) shows the positive relationship to the capital structure. All the data were regressed using multiple linear regressions through eviews.